2015
DOI: 10.1063/1.4918560
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism of magnetically doped topological insulators in CrxBi2−xTe3 thin films

Abstract: We investigated the effect of magnetic doping on magnetic and transport properties of Bi2Te3thin films. CrxBi2−xTe3 thin films with x = 0.03, 0.14, and 0.29 were grown epitaxially on mica substrate with low surface roughness (∼0.4 nm). It is found that Cr is an electron acceptor in Bi2Te3 and increases the magnetization of CrxBi2−xTe3. When x = 0.14 and 0.29,ferromagnetism appears in CrxBi2−xTe3 thin films, where anomalous Hall effect and weak localization of magnetoconductance were observed. The Curie tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Interestingly this model finds its applications in topological insulators, refs. [378,379], where it is observed that the magnetoconductance starts showing hysteresis behavior similar to magnetization as magnetic doping increases. This is called hysteric magnetoconductance phase.…”
Section: Topological Effectsmentioning
confidence: 99%
“…Interestingly this model finds its applications in topological insulators, refs. [378,379], where it is observed that the magnetoconductance starts showing hysteresis behavior similar to magnetization as magnetic doping increases. This is called hysteric magnetoconductance phase.…”
Section: Topological Effectsmentioning
confidence: 99%
“…Since the discovery of TIs, considerable experimental effort has been dedicated to achieve long-range magnetic order in two prototypical TIs, Bi 2 Se 3 and Bi 2 Te 3 , by doping with different TM atoms, such as Cr, Mn, or Fe, in both bulk and thin film geometries [17][18][19][20][21][22][23][24][25][26][27]. Significant theoretical work has also been undertaken to understand the mechanism of magnetism in transition metal (TM) doped TIs [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. For some of the magnetic TIs where the QAHE has been observed, such as Cr-doped (Bi,Sb) 2 Te 3 , it has been proposed that the mechanism driving the ferromagnetic transition is based on the Van Vleck spin susceptibility [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the sensitivity of Mn doped TI AHE sensor is much lower than other AHE sensor reported. Previously work on Cr doped Bi2Te3 [16] shows that Cr introduces much stronger magnetization in the system than Mn indicating that the sensitivity of AHE sensor based on it will be very high. In order to seek a much higher sensitivity AHE senor based on TI, in this work, we fabricate Hall effect sensors based on Cr-doped Bi2Te3 TI thin films.…”
mentioning
confidence: 99%